The Impact of ‘No Work, No Pay’ Policy on Industrial Actions: A Case Study of ASUU at the University of Lagos - Oluwabusayo Olanrewaju Oni; Mariam Gbajumo-Sheriff (Petra International Journal of Business Studies, 2025)
Trade unions regard the right to strike as a vital tool to counter low wages or unfavorable working conditions. This study explores the impact of the "No Work, No Pay" policy on industrial actions by the Academic Staff Union of Universities (ASUU) in Nigeria. Using a qualitative approach and a review of related literature, primary data were collected through structured interviews. The interview guide featured two sections: Section A addressed respondents' sociodemographic characteristics, while Section B focused on the study's core subject. The study's population consisted of 1,707 ASUU members, and 58 interviews were conducted across eight faculties at the University of Lagos, located on the Akoka campus. Data were analyzed using content and thematic analysis. Findings revealed that the "No Work, No Pay" policy has a significant influence on academic staff's willingness to engage in strikes and the frequency of such actions in the sector. The study concluded that the policy has a dual effect: it can deter strikes by encouraging alternative dispute resolution while reinforcing lecturers' determination due to perceived infringements on their rights. Therefore, the study recommended a continuous dialogue between lecturers and government authorities to address disputes constructively.